Rejoinder an opinion piece in response to the religious leaders who have asked for secular humanism to be included in Religious Studies examinations - Felderhof, M. C. (2015)
This article is a response to a published letter by some prominent religious leaders, including the former archbishop of Canterbury, Rowan Williams, pleading for the inclusion of secular humanism within national Religious Studies (RS) exams for school pupils. This briefing sets out some of the counter-arguments for doing so. They have to do with honesty in education, with practical considerations, with legality, with philosophical and theological concerns, with educational and pedagogical imperatives. The presence of secular humanism in religious education (RE) invariably leads to a secular and secularising study of religion which is undesirable if RE in school is to serve its primary purpose of leading to the spiritual and moral development of pupils. All of these together make a strong case for not doing what these leaders have suggested.
Keywords: Religious Education; atheistic critiques; RE and the law; Religious Studies exams; Secular Humanism